2015
DOI: 10.1120/jacmp.v16i6.5616
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of out‐of‐field dose components in high energy electron beams used in external beam radiotherapy

Abstract: The purpose of this work was to experimentally investigate the out‐of‐field dose in a water phantom, with several high energy electron beams used in external beam radiotherapy (RT). The study was carried out for 6, 9, 12, and 18 MeV electron beams, on three different linear accelerators, each equipped with a specific applicator. Measurements were performed in a water phantom, at different depths, for different applicator sizes, and off‐axis distances up to 70 cm from beam central axis (CAX). Thermoluminescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(55 reference statements)
2
9
0
Order By: Relevance
“…The characteristics of the nontarget dose from electron therapy are starkly different than those from photon therapy, and the magnitude of the nontarget dose from electron therapy is highly dependent on accelerator manufacturer, as shown in Fig. , and even based on specific applicator type . While out‐of‐field doses generally decrease with distance from the edge for electron therapy, this is less pronounced than for photon therapy (particularly for Elekta and Siemens accelerators), and the dose may show regions of increase, particularly around 20 cm from the field edge.…”
Section: Dose Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the nontarget dose from electron therapy are starkly different than those from photon therapy, and the magnitude of the nontarget dose from electron therapy is highly dependent on accelerator manufacturer, as shown in Fig. , and even based on specific applicator type . While out‐of‐field doses generally decrease with distance from the edge for electron therapy, this is less pronounced than for photon therapy (particularly for Elekta and Siemens accelerators), and the dose may show regions of increase, particularly around 20 cm from the field edge.…”
Section: Dose Estimatesmentioning
confidence: 99%
“…While out‐of‐field doses generally decrease with distance from the edge for electron therapy, this is less pronounced than for photon therapy (particularly for Elekta and Siemens accelerators), and the dose may show regions of increase, particularly around 20 cm from the field edge. The majority of the out‐of‐field dose is from scattered electrons, particularly scattered primary electrons or Compton scattered electrons originating in the lower trimmer . The increase in dose at ~20 cm from the field edge arises from scattered electrons originating from the rounded surface of the MLC .…”
Section: Dose Estimatesmentioning
confidence: 99%
“…Hospital physicists obtained radiotherapy and patient data from technical radiotherapy records for all included patients who received radiotherapy. For each of these patients, radiation treatment was reconstructed using a commercialized Treatment Planning System (TPS), Isogray®, in which patient images were replaced by anthropomorphic phantoms mimicking the anatomical dimensions of the patient in which the main organs of interest were contoured (16,17,18,19). Details about the methods have been previously described (20).…”
Section: Radiation Dosimetrymentioning
confidence: 99%
“…Alabdoaburas et al 17 measured the peripheral dose of electron beams by thermoluminescent dosimeter and EBT3 film for a Varian-type applicator. They found that the out-of-field dose from electron beams increases with the beam energy and the applicator size, and decreases with the distance from the beam central axis and the depth in water.…”
Section: Discussionmentioning
confidence: 99%